Finnish standardization panel pilot study: Preliminary observations and a research agenda - Heikkilä, Jussi T. S. (Journal of Standardisation, 2026)
Standardization ecosystems are arguably inseparable components of innovation ecosystems and national innovation systems. The design of standardization institutions may impact innovation incentives, appropriation of research and development investments and the rate and direction of technological progress. We evaluate the status of the Finnish standardization ecosystem and the role of standardization for the stakeholders of the Finnish standardization ecosystem. Extensive stakeholder interviews provided diverse perspectives of which the following saturated observations can be highlighted. First, the role and impacts of standards vary across industries, so the perspectives on the functioning of standardization systems vary accordingly. Second, standardization education is not systematic in Finland, indicating that standardization education could be improved to complement the learning by doing approach in organizations. Third, the role of standardization is expected to increase in the future, but geopolitical tensions cast a shadow on the functioning of the system. The pilot study provides one benchmark for the analysis of national standardization ecosystems in other (European) small open economies. We conclude by presenting a research agenda.